Inhibition factors in biofilm N removal systems treating wastes generated by amine based CO2 capture. (February 2016) - Henry, Ingrid A.; Einbu, Aslak; Svendsen, Hallvard F.; Bakke, Ingrid; ÿstgaard, Kjetill
Graphical abstract: Highlights: ⿢ Amine based CCS waste is suitable for BNR in pre-denitrification mode. ⿢ Organic loading led to heterotrophic enriched nitrifying MBBR with 80% efficiency. ⿢ Nitrification was inhibited at amine concentrations ranging from 9 to 120 mM. ⿢ Denitrification was stimulated at amine concentrations up to 100 mM. ⿢ Heterotrophic enriched are 5⿿20ÿ more sensitive than autotrophic enriched MBBRs to MEA or organics. Abstract: We have previously shown that biological nitrogen removal by pre-denitrification as illustrated may be a feasible approach for treating wastes generated by amine based CO2 capture. In order to identify limiting factors for successful up-scaling, we first compared the nitrifying activity of moving bed biofilm reactors (MBBR) with or without chronic exposure to organic loading in the form of acetate while monitoring population dynamics in the biofilms by pyro-sequencing. Our results show that the long-term abundance of heterotrophic bacteria is an essential factor in inhibition of nitrification efficiency. Secondly, the inhibition potential of the commonly applied amines monoethanolamine (MEA), 2-amino-2-methyl-1-propanol (AMP), diethanolamine (DEA), methyldiethanolamine (MDEA), piperazine (Pip), as well as MEA based reclaimer waste (RW) were tested on separate nitrifying and denitrifying MBBRs. Results show that nitrification was inhibited by 50% at EC50 concentrations from 9 to 120 mM, whereas denitrification was stimulated by all compounds at concentrations up to 100 mM. Nitrifying biofilms long-term adapted to organic loadings were 5⿿20 times more sensitive towards inhibition than those maintained without organic feeding, by both MEA and by organic loading. The crucial factor for the total process is therefore maintaining nitrification by avoiding overloading of amines or other organics in the second reactor.